Cloning of mutant genes of Klebsiellae pneumoniae resistant against BRL 41897A (KSL Mutants) - M. Kuswandi. (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2004)
Previous observations to identify Klebsiellae pneumoniae mutants (KSL) resistant to BRL41897A antibiotic (Kuswandi, 2002), using Southern blot dan SDS-PAGE analysis, showed that there were variation of TnphoA copy in each mutant and differentiation of outer membrane (OM and IROMP) of several mutants cell wall. In order to clone the gene which carries TnphoA from the KSL mutants, the chromosomal DNA fragments that had been ligated to pUC18 plasmid was transformed into E.coli host cells. The positive transformants of different mutants (KSL 19, KSL38 and KSL62) carrying TnphoA has been sequenced. The results showed that the three different transformants of the mutants had different genes inserted TnphoA.Key words: Resistant K.pneumoniae mutants -BRL41897A, clone, sequencing.